A preliminary study in to the viability of sponges as a proxy for sus scrofa (domesticus) lungs for ballistic evaluations. Issue 1 (January 2021) - Pullen, A E; Kieser, D C; Hooper, G; Plummer, T C H
Abstract: While tissue simulants are considered best practice for ballistic evaluations, there is an ongoing debate about the use of tissue simulant and their relevance and there are calls to improve models by making them more anatomically relevant by the introduction of bony structures and organs. Therefore; the aim of this study was to try and determine if sponges and/or ballistic gelatin may be a suitable proxy to porcine lungs using 5.56x45mm (MK262-MOD1). Four sample groups consisting of 10% ballistic gelatin blocks, lungs embedded in gelatin, kitchen sponges and car sponge in gelatin were evaluated. Analysis included determining the onset of yaw, time from impact to the onset of yaw, temporary and permanent cavity characteristics and energy deposition. The results indicated that the kitchen sponge and car sponge may be a suitable proxy to porcine lungs, however there were significant differences between the lung model and plain gelatin blocks and additional work should be carried out to investigate the suitability of sponges as a proxy to porcine lungs further.